(3eSGdc GdCagGe aj TQM TQGFY GdESdGes - (3GdTGej GdYGedj, CHh efUhQ, GHf GdTgjO GdKGfj, GHf GdTgjO GdKGfj, GdMSf Hf Rjf GdOjf Hf Ydj GdTGej GdYGedj, J (B1011(3g` (B1602(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg GdPj ChVM eSdc GdCagGe Edi JfbjM TQGFY GdESdGe (B... (3hHYO agPg fcJ eNJUQI hahGFO eMHQI hVYJgG Ydi cJGH TQGFY GdESdGe (B... (3GdWgGQI GSe ddhVhA hGdZSd hGdJjee Ydi hLg dg JCKjQs
(3BNQgG (B:s
(3BNQgG(B: (3hbO Qhj Yf RjO GdYGHOjf Ydj Hf GdMSjf YdjgeG GdSdGe EPG cfJe aj CFeI LhQ aGeVhG aj CMcGege hdG JTgQhG CfaSce aJbJdhG hGh Mce HePgH Cgd GdNdGa eY GecGf GfaGPg HGdMb (B... (3hGddg Gdehabs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 192s
(3GdPQjYI, L (B20: 246s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis